تأثير التحميل المتكرر على طاقة التحمل والسهم في الجوائز من البيتون عالي المقاومة - عبود أحمد; اندرواس غصون (Latakia University Journal -Engineering Sciences Series, 2018)
يقدم هذا البحث دراسة تجريبية لسلوك الجوائز- من البيتون عالي المقاومة- تحت تأثير التحميل الستاتيكي المتكرر، مع تحديد تأثير هذا النوع من التحميل على طاقة تحمل تلك الجوائز والسهوم الحاصلة فيها ومن ثمّ مقارنتها مع نظائرها في حالة التحميل المستمر. تمّ تصميم خلطة من البيتون عالي المقاومة وفقاً لأحكام الكود الأميركي ACI211.4R-93، ومن ثمَّ تحضير ستة وثلاثين جائزاً من تلك الخلطة، حيث تمَ اختبار تسعة جوائز تحت تأثير التحميل المستمر، في حين اختُبرت الجوائز المتبقية تحت تأثير التحميل المتكرر لعدد محدد من الدورات (5,10,15) دورة، وذلك ضمن مجال تحميل من الصفر حتى 65% أو75% أو 85% من الحمولة الدنيا المتوقعة لانهيار الجوائز تحت تأثير التحميل المستمر. لقد أظهرت النتائج أن للتحميل المتكرر تأثيراً إيجابياً على سلوك الجوائز البيتونية الخاضعة للانعطاف، وذلك من حيث ازدياد في طاقة تحمل تلك الجوائز مع انخفاض في قيمة السهم المرافق لحمولة الانهيار، وخاصة عندما يكون مجال التحميل من الصفر حتى 75% من الحمولة الدنيا المتوقعة لانهيار الجوائز تحت تأثير التحميل المستمر، وعند عدد محدد من الدورات (5 أو 10 أو 15 دورة). This research presents an empirical study about the behavior of High Strength Concrete beams under the static cyclic loading. It determines the influence of cyclic loading on the moment capacity and deflection of HSC beams. A comparison of the moment capacity and deflection in both kinds of loading (monotonic and cyclic loading) were achieved. High Strength Concrete mixture was designed, based on the specifications of the American code ACI 211.4R-93. Thirty six concrete beams were prepared, nine of them were tested under monotonic loading and the rest of beams were tested under cyclic loading. The cyclic loading was performed for (5,10,15) cycles, at a range from zero to 65%, 75%, 85% of the minimum expected monotonic load. The results showed that the cyclic loading have positive effect on the flexural behavior of HSC members, whereas the moment capacity increased and the deflection decreased, especially at a range from zero to 75% of the minimum expected monotonic load, when the number of cycles was 5,10,15.